A Descriptive Cross-Sectional Study on Clinical Profile and Outcome of Delirium in Trauma Patients in the Semi-Closed Intensive Care Unit of a Medical College - Singh, Alok Kumar; Keyal, Niraj Kumar; Chaudhary, Pankaj; Izahar, Mosarrat; Alam, Md Shahid (Birat Journal of Health Sciences, 2022)
Introduction: Delirium in trauma patients is common and underdiagnosed. Objectives: This study aimed to identify the risk factors and outcome of delirium in trauma patients in a mixed semi-closed intensive care unit. Methodology: This descriptive cross-sectional study was done on 77 patients of age 18 years or more admitted for more than 24 hours with the history of road traffic accidents, falls, drowning, physical assaults, and self- inflicted violence in a level three intensive care unit of the National Medical College for six months. The whole sampling method was used in our study and all cases during a given time were included in the study. The Confusion Assessment Method-ICU and Richmond Agitation Sedation Scale were used to diagnose delirium and level of arousal respectively. All data was transferred to the excel sheet and transferred to a statistical package for the social sciences-16. The Chi-square test and Fisher’s exact probability test were used to detect the difference between groups in the univariate analysis, as appropriate. The variables were analyzed using binary logistic regression. Any variables which had P<0.2 after the univariable risk regression and all other potential variables associated with the delirium were included for the multivariable risk regression. The level of significance was P<0.05. Result: Of the 77 ICU admissions 17(22.1%) developed delirium. Hyperactive delirium was the most common motor subtype 9(52.9%). The mean duration of delirium was 3.69±4.06 days. Age, hypertension, blood transfusion, and orthopedic trauma were identified as risk factors for delirium. Delirious patients had a longer length of stay in the ICU (7.0 ±4.6 vs 4.5±4.1 days) with no impact on the duration of mechanical ventilation, mortality, reintubation, and unplanned extubation. Conclusion: Age, hypertension, blood transfusion and orthopaedic trauma were identified as the risk factor for delirium in trauma patients that should be identified early to prevent complications such as longer length of stay in the ICU, longer duration of mechanical ventilation, mortality, reintubation and unplanned extubation.